New sporocarpic taxa in the phylum Glomeromycota: Sclerocarpum amazonicum gen. et sp. nov. in the family Glomeraceae (Glomerales) and Diversispora sporocarpia sp. nov. in the Diversisporaceae (Diversisporales) - Jobim, Khadija; Błaszkowski, Janusz; Niezgoda, Piotr; Koz?owska, Anna; Zubek, Szymon; Mleczko, Piotr; Chachu?a, Piotr; Ishikawa, Noemia Kazue; Goto, Bruno Tomio (Mycological Progress, 2019)
Of the nearly 300 species of the phylum Glomeromycota comprising arbuscular mycorrhizal fungi (AMF), only 24 were originally described to form glomoid spores in unorganized sporocarps with a peridium and a gleba, in which the spores are distributed randomly. However, the natural (molecular) phylogeny of most of these species remains unknown. We found unorganized sporocarps of two fungi-producing glomoid spores: one in the Amazonian forest in Brazil (tropical forest) and the second in a forest of Poland (temperate forest). The unique spore morphology of the two fungi suggested that they are undescribed species. Subsequent phylogenetic analyses of sequences of the small subunit–internal transcribed spacer–large subunit nrDNA region and the RPB1 gene confirmed this assumption and placed the Brazilian fungus in a separate clade at the rank of genus, very strongly divergent from its sister clade representing the genus Glomus sensu stricto in the family Glomeraceae (order Glomerales). The Polish fungus was accommodated in a sister clade to a clade grouping sequences of Diversispora epigaea, a fungus that also occasionally produces spores in sporocarps, belonging in the Diversisporaceae (Diversisporales). Consequently, the Brazilian fungus was here described as the new genus and new species Sclerocarpum gen. nov. and S. amazonicum sp. nov., respectively. The Polish fungus was described as D. sporocarpia sp. nov. In addition, the supposed reasons for the low representation of sporocarpic species in the Glomeromycota were discussed and the known distribution of sporocarp-producing Glomeromycota was outlined. © 2019, The Author(s).